Persepsi Risiko dan E-Trust dalam Mempengaruhi Purchase Intention di TikTok Shop: Studi Pada Pengguna di Kabupaten Kolaka - Rismal, Rismal; Kumalasari, Fitri; Stiadi, Muhamad (Innovative: Journal Of Social Science Research, 2025)
This research aims to examine the influence of risk perception and e-trust on purchase intention in TikTok Shop, with a focus on users in Kolaka Regency. A quantitative approach was employed, and data was gathered through an online questionnaire (Google Form). The study's population includes Kolaka Regency residents interested in shopping on the TikTok Shop marketplace. A total of 104 respondents were selected as the sample. Data analysis was performed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with Smart-PLS 3.0. The results indicate that risk perception and e-trust have a significant and positive impact on purchase intention in TikTok Shop.